The Existance of the Acte Van Dading Against the Resolution of Civil Case Lawsuit for Breach of Contract Based on the Case Study of Acte Van Dading Number 97/Pdt.G/2023/PN Slt - Az Zahra Putri, Anisa Rahmadhani; Soroinda, Disriani Latifah (Faculty of Law, Universitas Pekalongan, 2024)
The strength of a Settlement Agreement Act is equivalent to ha ruling issued by the court. The Settlement Agreement Act arises from a peace agreement made during the mediation process in front of a designated judge who has the authority to act as a mediator. This peace agreement does not carry executory legal power. This is because the Settlement Agreement Act is a settlement ruling issued by the district court, reflecting the true intent and agreement of the parties involved in a civil case directly. The mediator judge plays a fundamental role in mediation; the mediator must actively work to reconcile the parties in dispute, encouraging solutions that are fair and do not disadvantage one party over the other through a comprehensive problem-solving approach